The role of university extension in the context of the COVID-19 pandemic for families of children and adolescents with sickle cell disease: an experience report (Research, Society and Development, 2021)
Sickle Cell Disease (SCD) is the nomenclature used to designate a set of hemoglobinopathies resulting from a mutation in the beta-globin gene on chromosome 11. Among them, sickle cell anemia (HbSS) stands out for its high prevalence and high potential for morbidity and mortality. In this scenario, a family with a child or adolescent with SCD changes its biopsychosocial dynamic entirely, especially in the context of the COVID-19 pandemic, in which social distancing is recommended. This work intend to present the successful experience of the Extension Program "Educar Falciforme", linked to the Federal University of São João Del-Rei, a pillar in the support network for the management of patients and families with SDC, in a period that new processes, especially online, became necessary for the provision of healthcare for chronic non-communicable diseases (NCDs). The experience report and the bibliographical research were proposed as a methodology. Based on this experience, the results showed that despite adverse circumstances, virtual dynamics are necessary to maintain comprehensive care for families with SCD in a pandemic period. It is concluded that the extension is an important tool for support in the health community network.